Relative Efficacy of Quercetin Compared with Benzydamine Hydrochloride in Minor Aphthae: A Prospective, Parallel, Double Blind, Active Control, Preliminary Study. (13th November 2017) - Pandya, Maitreyi; Kalappanavar, Anupama N.; Annigeri, Rajeshwari G.; Rao, Dhanya S.
Abstract : Background and Objectives . Recurrent aphthous stomatitis is an inflammatory condition present since ancient era wherein numerous treatment modalities have been tried. But complete eradication of the disease has not been possible and hence newer agents are being introduced. One such agent is a flavonoid named quercetin with proven antioxidant, anti-inflammatory, and ulcer healing properties. Methods . 40 patients with minor aphthous ulcers were divided equally into two groups: A and B. Group A patients were advised to apply quercetin gel and Group B patients were advised to take benzydamine hydrochloride mouth wash. Clinical evaluation including assessment of ulcer size and pain score and questionnaire about the acceptability of both the drugs in terms of taste and ease of application was carried out. Each criterion was compared and statistically analyzed. Results . There was statistically significant reduction in the mean score of pain sensation and ulcer area in both the groups. Quercetin showed statistically highly significant ulcer size reduction as compared to benzydamine hydrochloride. Conclusion . From the present study, it is evident that quercetin is safe, well tolerated, and effective therapy which promotes complete ulcer healing in a short duration of time.